2010
DOI: 10.1016/j.hrthm.2009.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Transconduit puncture for catheter ablation of atrial tachycardia in a patient with extracardiac Fontan palliation

Abstract: Our patient is a 34 year old male with functionally single (left) ventricle, with tricuspid atresia but not pulmonary stenosis/atresia, and with atrial septal defect (ASD), ventricular septal defect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…At the same time, the access to the arrhythmia substrate within the atrium may be much more difficult with these two latter modifications of the Fontan procedure, particularly in case of ECC without fenestration, requiring puncture of the tunnel or conduit, or a retrograde approach through the aorta. This may render effective ablation procedure much more difficult or impossible [17,18]. An example of these difficulties is our patient No.…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, the access to the arrhythmia substrate within the atrium may be much more difficult with these two latter modifications of the Fontan procedure, particularly in case of ECC without fenestration, requiring puncture of the tunnel or conduit, or a retrograde approach through the aorta. This may render effective ablation procedure much more difficult or impossible [17,18]. An example of these difficulties is our patient No.…”
Section: Discussionmentioning
confidence: 96%
“…75 Difficulties crossing the Gore-tex tube resulted in deformation of a radiofrequency-powered transseptal needle. Efforts to position the dilator across the baffle failed.…”
Section: Managing Arrhythmias With the Standard Extracardiac Fontanmentioning
confidence: 99%
“…It was cautiously concluded that further studies are required to determine the safety of this procedure. 75 Safety hinges, in large part, on the premise that, over time, the inflammatory process results in fibrotic adhesion of the conduit to the pulmonary venous atrium, so as to eliminate the space between these 2 structures. Although this may be true in some, it cannot be predicted with certainty.…”
Section: Managing Arrhythmias With the Standard Extracardiac Fontanmentioning
confidence: 99%
“…Successful ablation was performed in an 11-year-old child with a double-inlet left ventricle, who underwent extracardiac Fontan at age 3. Dave et al 24 also reported "Transconduit puncture for catheter ablation of atrial tachycardia in a patient with extracardiac Fontan palliation." Successful ablation was performed in a 34-year-old patient with tricuspid atresia, who underwent Fontan conversion from an atriopulmonary Fontan to extracardiac Fontan at age 30.…”
Section: Advantage 4: Atrial Access For Electrophysiology Study May Smentioning
confidence: 99%